Insufficiency of finger flexors and extensors and its importance for hand function: A clinical and electromyographic investigation. (November 2015) - Lewit, Karel; Čihák, Radomír; Lepšíková, Magdalena
Abstract : Introduction: The basic function of the hand is prehension. The muscles of the forearm involved in prehension, the flexors and extensors of the wrist and fingers, attach at the epicondyles of the humerus, at the radius and ulna. Overstrain causes epicondylar pain. The cause of this phenomenon is passive insufficiency of muscles spanning several joints, in this case of the flexor digitorum profundus of the upper extremity, held in extension. Aim: To explore insufficiency of muscles electromyographically. Method and results: Activity of the flexors and extensors of the forearm was registered by surface electromyography, and this showed reduced activity when flexion of the end-phalanges was caused only by passive muscular insufficiency. Conclusion: These observations prove that carrying objects by the flexed end-phalanges keeping the muscles of the forearm relaxed is important for treatment and prevention of epicondylar pain. There is, however, an exception in extremely hypermobile subjects.